Mathematical creative thinking ability viewed from the types of personality on CPS learning model - Prasetiawan, Aditya Hendra; Junaedi, Iwan; Soedjoko, Edy (Department of Mathematics, Universitas Negeri Semarang, 2018)
The purpose of this research was to describe the learning quality of CPS model towards mathematical creative thinking ability of students viewed from personality types. This research was a mixed method is the type of this research. Mathematical Creative Thinking Skill Test (MCTST) was analyzed quantitatively by classical completeness test and different test average. Furthermore, MCTST was also analyzed qualitatively to gain the description of mathematical creative thinking ability viewed from personality types. The results showed that the quality of CPS mathematics learning model in good category. The artisans subject did not complete mathematical creative thinking aspects, especially fluency and flexibility aspects, guardians subject met all four aspects of mathematical creative thinking, the idealist subject did not meet mathematical creative thinking aspects, especially originality and elaboration aspects, and the rational subject met all four aspects of mathematical creative thinking.